2000
DOI: 10.1111/j.1540-8159.2000.tb07014.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Optimization of Resting and Exercise Atrioventricular Interval Using a Peak Endocardial Acceleration Sensor: Validation with Doppler Echocardiography and Direct Cardiac Output Measurements

Abstract: LEUNG, S.-K., ET AL.: Automatic Optimization of Resting and Exercise Atrioventricular Interval Using a Peak Endocardial Acceleration Sensor: Validation with Doppler Echocardiography and Direct Cardiac Output Measurements. Peak endocardial acceleration (PEA) measured by an implantable acceleration sensor inside the tip of a pacing lead reflects ventricular filling and myocardial contractility. The contri bution of the plateau phase of PEA as an indicator of optimal ventricular filling, hence of the appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Previous studies on the relationship between the amplitude of the first heart sound (S1) and cardiac contractility offer a way to reconcile the measurements. Animal experiments and invasive and non-invasive clinical trails have shown that there is a very close relationship between the amplitude of the first heart sound (S1) and the cardiac contractility [9-12]. The animal study by Hansen et al [9] showed that changes in the amplitude of the first heart sound are found to correlate closely with changes in the maximum rate of rise of left ventricular pressure (r = 0.9551, P < 0.001) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the relationship between the amplitude of the first heart sound (S1) and cardiac contractility offer a way to reconcile the measurements. Animal experiments and invasive and non-invasive clinical trails have shown that there is a very close relationship between the amplitude of the first heart sound (S1) and the cardiac contractility [9-12]. The animal study by Hansen et al [9] showed that changes in the amplitude of the first heart sound are found to correlate closely with changes in the maximum rate of rise of left ventricular pressure (r = 0.9551, P < 0.001) [9].…”
Section: Introductionmentioning
confidence: 99%
“…28 In a report on patients with a singlelead VDD pacemaker, 9% developed AF over a follow-up of 5.5 years. (28)(29). Thus, the incidence of AF between DDD and VDD appears comparable.…”
Section: Ams In Vdd Pacemakersmentioning
confidence: 73%
“…Although reprogramming to a non-tracking mode (such as DVI, DDI or DDIR) prevents this clinical event, these modes do not provide appropriate AV synchrony if the sinus rate exceeds the programmed lower rate. (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) Limitation of the upper tracking rate only partly addresses this problem and may compromise exercise capacity or lead to symptoms from pacemaker Wenckebach behaviour at relatively slow rates. In response to this clinical dilemma, a variety of mode-switching algorithms has been devised that are meant to prevent tracking of pathological atrial tachy-arrhythmias while allowing ventricular pacing that is synchronous with the atrial electrocardiogram during sinus rhythm [17][18][19].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…31,32 Similar results were obtained in patients tested during electrophysiologic studies using an external system; changes in PEA were linearly related to the RV dp/dt during dobutamine infusion. 33 The algorithm is now automatic. In 13 patients with end-stage heart failure implanted with a DDD-PEA device with a custom lead arrangement, PEA level during RV, LV, and biventricular (BiV) pacing were compared.…”
Section: Clinical Resultsmentioning
confidence: 99%